Indonesia’s Ideological Convergence : Emerging Trend in Islamic Regulations ? - Arifianto, Alexander Raymond (2018)
There is an emerging ideological convergence among activists from different Indonesian Islamic groups toward a more Shariah-oriented outlook. Such a convergence can be seen from the joint efforts of these activists to enact local Islamic regulations in various Indonesian regions.